Medication safety and rare side effect of carbamazepine: A case report - Zahra Yazdani; Shaghayegh Roofeh (Tehran University of Medical Sciences, 2023)
Introduction: Medicines are the most widely used interventions in health care and adverse drug reactions alone are responsible for 5-10% of hospitalizations in elderly patients. Carbamazepine is an anticonvulsant drug and skin rash is one of its rare symptoms of it. It requires immediate medical attention and is sometimes life-threatening. Case Report: This case report is about a 72-year-old woman who witnessed the interaction of rivaroxaban and carbamazepine, and the side effects of carbamazepine simultaneously. Conclusion: Patient participation and patient-centered tools are needed to promote patient safety.